Fugacity-based multimedia transport modeling and risk assessment of PAHs in Urumqi - Junxuan Ma; Nuerla Ailijiang; Anwar Mamat; Yixian Wu; Xiaoxiao Luo; Min Li (Scientific Reports)
Abstract Currently, there is a lack of a comprehensive understanding of the behavior of polycyclic aromatic hydrocarbons (PAHs) in complex multimedia urban environmental systems. Taking Urumqi City as a case study, we developed an integrated multimedia urban environmental model to simulate the inter-media transport processes of PAHs across air, water, soil, sediment, vegetation, and impervious surfaces. The predictive results of this model were in good agreement with the actual monitoring data from 2021, confirming its accuracy. Notably, the simulated data for 2021 indicate that the total amount of PAHs in the soil reached 1.06 × 106 kg, accounting for 97.44% of the total PAHs in Urumqi City, highlighting soil as the primary sink for PAHs. Further analysis of transport fluxes revealed that atmospheric transfer pathways to soil and vegetation are the main mechanisms driving the distribution of PAHs in urban environments. Additionally, sensitivity analysis identified temperature, soil, and vegetation-related parameters as the primary factors influencing PAHs. Based on the simulated concentration, the risk assessment results showed that soil PAHs had a higher risk of carcinogenesis to human body. This study deepens our understanding of the behavior of PAHs in urban environments and provides insights into how human activities affect the fate and transformation of these contaminants in multimedia urban systems.